An Evaluation of the Presence of Spin in the Abstracts of Tonsillectomy Systematic Reviews. (3rd September 2020) - Cooper, Craig M.; Johnson, Austin; Gray, Harrison; Vassar, Matt
Abstract : Objectives/Hypothesis: Spin—the practice of adding or omitting information intentionally or unintentionally to make the results of a study more favorable—may influence clinical decision making, especially when present in study abstracts. Here, we quantify and characterize the presence of spin in the abstracts of systematic reviews regarding tonsillectomy. Methods: This study is an analysis of systematic review abstracts. Searches were conducted on September 23, 2019 on PubMed and Embase using the advanced search feature to retrieve systematic reviews regarding tonsillectomies. The nine most severe forms of spin were then evaluated. Spin was classified by two investigators in parallel, with each blinded to the classifications of the other. Study characteristics were also recorded in duplicate. Consensus meetings between investigators were held to resolve disagreements. Results: In the 85 included systematic reviews, at least one form of spin was present in 44.7% (38/85) of abstracts. Journals with higher impact factors were less likely to contain spin in the abstracts of systematic reviews (point biserial correlation coefficient of −0.30). No statistically significant associations were found between the presence of spin and intervention type ( P = .56) or adherence to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses ( P = .08); however, there was a significant association between spin and funding source ( P = .03). Conclusions: Spin was common in the abstracts of our sample of tonsillectomy systematic reviews. Researchers, clinicians, and peer reviewers could benefit from learning to recognize spin in medical literature. Further research is needed into the effects of spin on clinical decision making. Level of Evidence: NA Laryngoscope, 131:E727–E731, 2021